Financial service providers: Does it matter if banks don't behave ethically?. (30th August 2018) - Patterson, Zoe; McEachern, Morven G.
Abstract: The ethical consumer literature predominantly concentrates on fast‐moving consuming goods and thus, neglects insights to consumer behaviour within ethical services. As the financial services sector continues to grow in the UK, this paper addresses this anomaly by providing further insight into consumers and their ethical banking practices. More specifically, it examines their motivations as well as the trade‐offs and barriers which prevent greater uptake. Using a combination of in‐depth interviews and projective techniques, the research draws on Freestone and McGoldrick's model to reveal a lack of awareness towards ethical financial service providers and sheds light on various perceptions regarding what constitutes an ethical financial service. Additionally, numerous underlying personal benefits of ethical financial services became apparent alongside consumer expectations of customer care. In conclusion, our findings help to create a revised model which identifies more precisely the stages of ethical awareness, motivation and behaviour of ethical consumers both in the context of ethical financial services but also ethical consumption practices in general.